Policy effects of reduced pension contribution rate on innovation input--Empirical evidence from Zhejiang and Shandong provinces. - Zimian He; Jianwei Xu (PLoS ONE)
Reducing pension insurance rates is an important measure for lowering the burden on enterprises. Does this measure encourage enterprises to invest in innovation? This study uses provincial panel data of China during 2000-2017 to analyze the reduction in the proportion of enterprise contributions to pension insurance in Zhejiang and Shandong provinces as a quasi-natural experiment. Specifically, it uses the synthetic control method to construct a counterfactual state of the treatment group, and analyzes the effect of fee reduction policy on enterprise innovation input. Taking R&D intensity as a proxy for innovation input, the study finds that the cost reduction policy has a significant promoting effect on innovation input. Although the reduction of pension insurance rate in Shandong is smaller than that in Zhejiang, the net effect of policy on R&D intensity is higher than that in Zhejiang. This study uses a placebo test, permutation test, and difference-in-differences method to carry out robustness checks, and confirms that the results are reliable, showing that the reduction of pension premium is conducive to the increase in enterprises' R&D intensity. However, owing to different economic development cycles in different regions, the net effect of pension premium reduction on enterprise innovation shows heterogeneity.